2018
DOI: 10.1159/000492051
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Milan System for Risk Stratification and Its Comparison with a Previous Reporting System of Parotid Gland Cytopathology in a Tertiary Care Centre

Abstract: Objective: To compare the recently proposed Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) with the four-tiered reporting system (FTRS) followed at our institute. Methods: Parotid gland fine-needle aspirates reported over a period of 5 years were analysed. These aspirates had been placed into 4 categories according to the FTRS: unsatisfactory (UNS), no evidence of malignancy/negative (NEG), inconclusive for malignancy (INC), and diagnostic for malignancy/positive (POS). Aspirates with follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 13 publications
7
22
1
Order By: Relevance
“…The RON and the ROM were 93.5% and 41.9%, respectively. The ROM for the SUMP category of submandibular FNA cases was similar to the ROM of 42% in a meta‐analysis review and slightly higher than the 35% target rate of the MSRSGC and the 37.5% rate in a comprehensive literature review, even though significant variation is expected for this indeterminate category as well (ROM, 37.5% ± 24.7%) . Although the ROMs of AUS (28%) and SUMP (42%) overlapped or were close in our study and others, the RONs of AUS (48%) and SUMP (94%) were very different (Table ), and this was in keeping with the definitions of AUS (indefinite for a neoplasm) and SUMP (diagnostic of a neoplasm but an uncertain type) and supported different approaches for the management of these categories (eg, repeat FNA vs upfront surgery).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The RON and the ROM were 93.5% and 41.9%, respectively. The ROM for the SUMP category of submandibular FNA cases was similar to the ROM of 42% in a meta‐analysis review and slightly higher than the 35% target rate of the MSRSGC and the 37.5% rate in a comprehensive literature review, even though significant variation is expected for this indeterminate category as well (ROM, 37.5% ± 24.7%) . Although the ROMs of AUS (28%) and SUMP (42%) overlapped or were close in our study and others, the RONs of AUS (48%) and SUMP (94%) were very different (Table ), and this was in keeping with the definitions of AUS (indefinite for a neoplasm) and SUMP (diagnostic of a neoplasm but an uncertain type) and supported different approaches for the management of these categories (eg, repeat FNA vs upfront surgery).…”
Section: Discussionsupporting
confidence: 73%
“…In this study, 21.4% of submandibular FNA cases (157 of 734) were diagnosed as nondiagnostic, and this was much higher than the maximum target rate of 10% suggested by the MSRSGC and the 13.5% reported for this category by Song et al Moreover, in 2 separate comprehensive reviews of the literature on salivary gland FNA conducted by Wei et al and Farahani and Baloch, the nondiagnostic rates ranged from 1.1% to 7.8% and from <1% to 44%, respectively . In addition, our study showed that there was high variability in the nondiagnostic rates between institutions, which ranged from 0% to 50%, with 7 of the 15 institutions having nondiagnostic rates ≤ 10%.…”
Section: Discussioncontrasting
confidence: 52%
“…Since the Milan system was proposed, several studies have shown its diagnostic utility by examining the risk of malignancy (ROM) for each category of the system . Though Hollyfield et al assessed interobserver reliability within MSRSGC focusing only on AUS and SUMP categories but none has studied the overall interobserver variability in MSRSGC that too among pathologists with different years of experience in cytopathology.…”
Section: Introductionsupporting
confidence: 56%
“…Most of the authors have assessed the utility and applicability of MSRSGC primarily focusing on risk stratification of salivary gland cytology. The reported ROM in these studies are mostly concordant with ROM published by the MSRSGC . Layfield et al compared FNA diagnoses from a prior study with specific diagnoses with corresponding MSRSGC diagnoses and found that MSRSGC was comparable with the original reported diagnoses in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…To create a standardized practical reporting system that aids in the communication between clinicians and cytopathologists, advance patient care, as well as allow exchange of study data between various laboratories, the American Society of Cytopathology (ASC) and the International Academy of Cytology (IAC) have suggested a classification system: The Milan System for Reporting Salivary Gland Cytology (MSRSGC) (8). This system is similar to the cytological reporting systems of the thyroid, cervix, and the pancreaticobiliary, respiratory and urinary systems (5). MSRSGC contains six diagnostic categories that are associated with proposed risk of malignancy (ROM) and recommendations for clinical intervention (2).…”
Section: Introductionmentioning
confidence: 99%